The Characteristics of Cervical Cancer Patients Who Underwent a Radical Hysterectomy at Sanglah Hospital Denpasar in 2015 - Mahendra, I Nyoman Bayu (BALI MEDICAL JOURNAL; Vol 5 No 2 (2016), 2016)
Background: Cervical cancer is the most common gynecologic cancer in women. It is the main cause  of cancer-related death in women in developing countries. Cervical cancer in Indonesia is the second  most cancer affecting Indonesian women and the prevalence is relatively stable in the last 30 years.  Cervical cancer was closely related to the histologic type of itself. A squamous cell carcinoma has a  specific route of local spreading and a lymphatic route. The sample of this study are cervical cancer  patients who underwent a radical hysterectomy from January 1 to December 31, 2015 in Sanglah  Hospital Denpasar, Bali. The aim of this study is to discover the characteristics of the patients by age,  parity, education level, marital status, sexual activity, the first symptoms and the early screening done,  and the clinical staging. Methods: This descriptive study involved 20 patients in Sanglah Hospital Denpasar who had a radical hysterectomy from January 1 until December 31, 2015. The characteristics are gathered from the patients’ medical record. Results: The most cases done radical hysterectomy between 41-45 years old which proportion was 40%, the most parity was parity 2 (60%), elementary school was the most education level (35%), all of the samples only married once and sexually active, the most first symptom was vaginal bleeding (55%), only 10% had pap smear as early detection, and the most clinical stage was stage IIB (50%).
Keywords: cervical cancer, radical hysterectomy, patient characteristic